Purification and Characterization of protease from Zahdi dates plam seeds (Phoenix dactylifera L.) - Baghdad Science Journal (مجلة بغداد للعلوم, 2009)
Proteinases (E.C.3.4.21) family are widely distributed in the nature; it was present in animals tissues , plants and microbial cell . Protease was purified from Zahdi seed (Phoenix dactylifera L.) by several steps included ammonium sulphite ppt (75%) saturation and dialyzed against the 80mM sodium phosphate buffer at pH 7.5 . The enzyme specific activity was 407.62 unit/mg protein. The obtained extract was purified by DEAE-Cellulose column followed by gel filtration through Sephacyl S-200 column .The enzyme specific activity ,yield and purification fold were 1873.49 unit/mg protein, 22.99 and 58.42% respectively. The results of protease characterization showed that the molecular weight was 25118 daltons as determined by gel filtration. The optimum temperature of the enzyme activity 35 C for 15 minutes and that for stability was 45 C for 15 minutes, using sodium phosphate buffer at pH 7.5, The optimum pH for the enzyme stability and activity were 8.5 for 15 minute and 7.5 respectively.